2014
DOI: 10.1016/j.watres.2013.10.056
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of wastewater and recycled water quality: A comparison of lines of evidence from in vitro, in vivo and chemical analyses

Abstract: We investigated water quality at an advanced water reclamation plant and three conventional wastewater treatment plants using an "ecotoxicity toolbox" consisting of three complementary analyses (chemical analysis, in vitro bioanalysis and in situ biological monitoring), with a focus on endocrine disruption. The in vitro bioassays were chosen to provide an appropriately wide coverage of biological effects relevant to managed aquifer recharge and environmental discharge of treated wastewater, and included bioass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
58
2
1

Year Published

2015
2015
2017
2017

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 105 publications
(73 citation statements)
references
References 24 publications
12
58
2
1
Order By: Relevance
“…Thus all samples were below the EBT-TTEQ of 14 ng/L. Previous studies have likewise reported no androgenic activity in treated water such as drinking or recycled water Leusch et al, 2014aLeusch et al, , 2014bVan der Linden et al, 2008).…”
Section: Endocrine Activitymentioning
confidence: 61%
“…Thus all samples were below the EBT-TTEQ of 14 ng/L. Previous studies have likewise reported no androgenic activity in treated water such as drinking or recycled water Leusch et al, 2014aLeusch et al, , 2014bVan der Linden et al, 2008).…”
Section: Endocrine Activitymentioning
confidence: 61%
“…There are only a few studies reporting the TrOC profile of raw sewage generated from small towns in Australia (Le-Minh et al, 2010;Trinh et al, 2012b;Leusch et al, 2014;Scott et al, 2014). Thus a critical discussion regarding the frequency and concentration of the TrOCs detected in the influent wastewater is necessary to facilitate assessment of the TrOC removal capacity of the MBRs.…”
Section: Occurrence Of Trocs In Influent Wastewatermentioning
confidence: 99%
“…Several studies have assessed the occurrence of TrOCs in wastewater originating from various catchment areas including agricultural, rural, urban and industrial wastewater catchments Scott et al, 2014) and the treated effluent produced by various types and scales of WWTPs (Coleman et al, 2008;Ying et al, 2009;Leusch et al, 2014). However, only a few studies reported the TrOC profile of raw sewage generated from small Australian towns (Braga et al, 2005;Coleman et al, 2008;Leusch et al, 2014), particularly those which are tourist destinations (Le-Minh et al, 2010;Trinh et al, 2012b). Wastewater from small resort towns can have distinct characteristics in terms of volume of wastewater produced and also the frequency and concentration in which TrOCs may occur.…”
Section: Introductionmentioning
confidence: 99%
“…Samples were also collected and analyzed for a range of commonly occurring endocrine disrupting compounds (EDCs), pharmaceuticals and personal care products (PPCPs), and herbicides according to previously described methodologies (Tan et al, 2007;Reungoat et al, 2010;Leusch et al, 2014). The full list of analyzed compounds comprises 116 chemicals in the Queensland Health Forensic and Scientific Services (QHFSS) EDC, PPCP and herbicide screening suites, and is provided in the supplementary material (Supplementary Table 1).…”
Section: Chemical Analysismentioning
confidence: 99%